Oxidative Stress and Antioxidative Therapy in Pulmonary Arterial Hypertension - Dan Xu; Ya-Hui Hu; Xue Gou; Feng-Yang Li; Xi-Yu-Chen Yang; Yun-Man Li; Feng Chen (Molecules, 2022)
Pulmonary arterial hypertension (PAH) is clinically characterized by a progressive increase in pulmonary artery pressure, followed by right ventricular hypertrophy and subsequently right heart failure. The underlying mechanism of PAH includes endothelial dysfunction and intimal smooth muscle proliferation. Numerous studies have shown that oxidative stress is critical in the pathophysiology of PAH and involves changes in reactive oxygen species (ROS), reactive nitrogen (RNS), and nitric oxide (NO) signaling pathways. Disrupted ROS and NO signaling pathways cause the proliferation of pulmonary arterial endothelial cells (PAECs) and pulmonary vascular smooth muscle cells (PASMCs), resulting in DNA damage, metabolic abnormalities, and vascular remodeling. Antioxidant treatment has become a main area of research for the treatment of PAH. This review mainly introduces oxidative stress in the pathogenesis of PAH and antioxidative therapies and explains why targeting oxidative stress is a valid strategy for PAH treatment.